Definition of Food Safety Criteria for Bacteria Food-Borne Pathogens in Ready to Eat products - Bovo, Federica <1983> (Alma Mater Studiorum - Università di Bologna, 2015)

(untitled)
The aims of this research study is to explore the opportunity to set up Performance Objectives (POs) parameters for specific risks in RTE products to propose for food industries and food authorities. In fact, even if microbiological criteria for Salmonella and Listeria monocytogenes Ready-to-Eat (RTE) products are included in the European Regulation, these parameters are not risk based and no microbiological criteria for Bacillus cereus in RTE products is present. For these reasons the behaviour of Salmonella enterica in RTE mixed salad, the microbiological characteristics in RTE spelt salad, and the definition of POs for Bacillus cereus and Listeria monocytogenes in RTE spelt salad has been assessed. Based on the data produced can be drawn the following conclusions: 1. A rapid growth of Salmonella enterica may occurr in mixed ingredient salads, and strict temperature control during the production chain of the product is critical. 2. Spelt salad is characterized by the presence of high number of Lactic Acid Bacteria. Listeria spp. and Enterobacteriaceae, on the contrary, did not grow during the shlef life, probably due to the relevant metabolic activity of LAB. 3. The use of spelt and cheese compliant with the suggested POs might significantly reduce the incidence of foodborne intoxications due to Bacillus cereus and Listeria monocytogenes and the proportions of recalls, causing huge economic losses for food companies commercializing RTE products. 4. The approach to calculate the POs values and reported in my work can be easily adapted to different food/risk combination as well as to any changes in the formulation of the same food products. 5. The optimized sampling plans in term of number of samples to collect can be derive in order to verify the compliance to POs values selected.